Healthy Ramadan with Rosella Herbal Drink: an Initiative by DPC ASPETRI Surabaya for the People of Surabaya - Wibowo, Teguh Setiawan; Hidayati, Nurul; Kholiq, Abdul (Eastasouth Institute, 2025)
The holy month of Ramadan is a significant period for Muslims to observe fasting. During fasting, maintaining a strong immune system is crucial for staying healthy and energetic. One natural way to boost immunity is by consuming herbal beverages. In support of public health during Ramadan, the Regional Leadership Council (DPC) of the Indonesian Association of Traditional Herbal Medicine Practitioners (Aspetri) in Surabaya organized a community service program by distributing fresh rosella (Hibiscus sabdariffa) herbal drinks. This initiative aimed to raise public awareness about the benefits of herbal medicine in maintaining immunity and to promote the use of natural remedies in daily life. The program involved distributing fresh rosella herbal drinks for free at several strategic locations in Surabaya. Rosella was chosen due to its high antioxidant content, vitamin C, and other bioactive compounds that contribute to boosting the immune system and maintaining metabolic balance during fasting. In addition to distributing herbal drinks, educational sessions were conducted to inform the public about the health benefits of herbal remedies. The results of this initiative showed a high level of enthusiasm among the public regarding the consumption of herbal drinks as a healthy alternative during Ramadan. This program also had a positive impact on increasing public awareness of preventive health measures through herbal-based solutions. Furthermore, it strengthened the role of DPC Aspetri Surabaya in educating and advocating for the integration of herbal medicine into a healthy lifestyle. Moving forward, it is hoped that this program can be continued and expanded to cover more areas and include a wider variety of natural herbal beverages.